Assessment of attachment patterns in preterm children, comparative study with children born at term - Gutierrez, María José (2020)
Preliminary results of an ongoing investigation are presented in a public health center in the city of La Banda, province of Santiago del Estero, which aims to assess the incidence of prematurity in the child's attachment style. Children born preterm and full-term are evaluated during the second year of life (12-24 months). It is based on the idea that some characteristics of prematurity, such as hospitalization in neonatology and behavioral and emotional manifestations different from that of children born at term, can introduce differences in the way of linking. The sample consisted of 30 mother-baby dyads corresponding to two groups: group A, composed of mother- premature baby dyads, and a control group B, composed of mother-non-premature baby dyads, 15 of these correspond to mother/premature son and 15 to mother/non premature child. Fifteen girls and 15 males were studied. Healthy children were selected for the non-premature children control group (without previous pathologies). The mothers were between 22 and 37 years old and the children between 12 and 24 months old. To assess the attachment, the Argentine Procedure of the Strange Situation scale was used (Rodríguez and Oiberman, 2013) and socio-demographic information of certain variables that could be associated with the quality of attachment of infants with their mothers (maternal age, marital status, maternal work, child's gender and time of child's admission) was compiled. The Argentine Procedure of the Strange Situation is a controlled laboratory procedure consisting of observation in a double-mirror room, where the infant and his mother are evaluated in 8 episodes of 3 minutes each, in which the mother separates from and meets with her son, together with the presence of a stranger. For the statistical analysis of the data obtained, the statistical package for social sciences was used (SPSS). The research has the endorsement of the Institutional Committee of Ethics of Research in Health (CIEIS) corresponding to the Ministry of Health and Social development of Santiago del Estero, which certifies that the investigation complies with the ethical requirements. The results show that there are no statistical significant differences among the groups studied in the quality of attachment. Although it can be observed that the percentage of safe attachment is lower in premature infants in relation to children born at term, 60 % and 73 % respectively, this difference does not become significant at the statistical level. It should be taken into account that in this study we worked with a small simple; perhaps in a broader number of members of each group the results have significant differences. Similarly, no relationship was found between the socio-demographic variables studied and the style of attachment of the child. It was found that, in the case of premature born children, the time of hospitalization is related to the quality of attachment, most children who had a safe attachment style are those who had fewer days of hospitalization (less than 15 days). This study may be considered one of the first in South America to analyze the frequency of adherence patterns in premature early childhood, with the use of the argentine adaptation of the instrument that has more validation in the subject of attachment. These first results of the research in progress have certain limitations: one of them is the number of cases analyzed, and a second one was that the work was done with moderate and late preterm. It would be interesting to analyze the results of a study including children born with extreme prematurity (before 28 weeks).